Modelos dinâmicos: uma aplicação ao mercado de soja do Brasil - Moreira Leite, Carlos Antônio; L Ribeiro do Vale, Sonia Maria (Revista Ceres, 2025)
This work is concerned with an application of dynamic econometric models in policy analysis. For this purpose, an econometric model was employed for the soybean subsector and elasticities for the short and long runs were estimated.